Use of oral rehydration solution by mothers of under-five children in a rural area of Kancheepuram district, Tamil Nadu: a KAP study - M., Muthulakshmi; S., Gopalakrishnan (International Journal Of Community Medicine And Public Health, 2017)
Background: Diarrhoea is defined as the passage of loose, liquid or watery stools more than three times a day. Globally, diarrhoeal disease is the second leading cause of death in children under five years of age. Timely management of the children with ORS has substantially declined the morbidity and mortality from acute infectious diarrhoea. This study was planned with an objective to find out the knowledge, attitude and practice about the use of ORS among mothers of under five children. Methods: This is a cross sectional descriptive study carried out in the rural field practice area attached to a medical college in Kancheepuram district. Using simple random sampling method, the study group of 450 mothers of under-five children were identified. The data was collected using a pretested structured questionnaire containing 10 questions for assessing the knowledge and 8 for attitude and practice each. The answers were scored accordingly. Data was analysed using SPSS 17 software. Knowledge, attitude and practice were calculated using percentages. Results: It is observed that 72% had adequate knowledge, 92% had positive attitude and 94% had good practice regarding the use of ORS among mothers of under-five children. Conclusions: In this study, most of the mothers had adequate knowledge, attitude and practice about the use of ORS. However, knowledge, attitude and practice of mothers towards use of ORS for the treatment of diarrhoea need a little more improvement. This improvement can be achieved through effective health education strategies